Community Participation in Flood Mitigation Programs and Its Effect on Social Resilience in Semarang City - Sulaeman, Nyta; Sawar, Aldy (Generasi Sains Indonesia, 2025)
Flooding remains a recurrent threat to urban coastal areas in Indonesia, and Semarang City has been one of the most vulnerable cities in this regard. This study examines how community participation in flood mitigation programs contributes to the development of social resilience. Using a qualitative case study design, data were collected through interviews, focus group discussions, and direct observation in three flood-prone neighborhoods: Tambak Lorok, Kaligawe, and Tlogosari. The results show that participation takes various forms, including mangrove planting, drainage cleaning, and community-based training programs. These activities not only reduce physical risks but also build trust, solidarity, and adaptive capacities within communities. However, challenges remain, such as socio-economic disparities that affect inclusiveness, limited trust in institutional support, and the sustainability of participation over time. The findings highlight that while community engagement is central to resilience-building, it requires supportive governance, long-term commitment, and inclusive approaches to ensure effectiveness. This study contributes to the understanding of disaster risk reduction by emphasizing the synergy between grassroots participation and institutional frameworks. Strengthening this synergy is essential for developing resilience strategies that are not only reactive to crises but also proactive, inclusive, and sustainable.